Green Production and Characterization of Cadmium Nanoparticle by Phanerochaete Chrysosporium Secretion - Azian Mohd Suhaimi (School of Bioprocess Engineering, University Malaysia Perlis, 2019)
To extract Phanerochaete chrysosporium secretion and synthesize the cadmium nanoparticle by the reduction of cadmium nitrate. To characterize the obtained cadmium nanoparticle by morphological and structural analyses. To evaluate the antimicrobial potential of the synthesized cadmium nanoparticle.